Identifying Key Factors Shaping New Users' Intentions in Mobile Investment Applications - Haris, Abdul (AI Society & STMIK Indonesia, 2024)
This paper seeks to examine the key factors predicting the behavioral intentions of mobile investment app users. By understanding these influencing factors, the ultimate goal is to encourage more people to adopt and accept these apps. Adopting an integrated approach, the research combines different UTAUT2 (Unified Theory of Acceptance and Use of Technology 2) constructs for hypothesis development and to evaluate the effects on users’ adoption and behavior use of such platforms. Through an online survey among 161 users of popular mobile investing applications in Indonesia and applying structural equation modeling for analysis with the SmartPLS statistical tool, this research contributes empirical evidence on factors that drive user behavior in the mobile investment domain. The final model provided a good basis for proving the hypotheses presented and the factors can account for 65.6% of the variability in mobile investment app behavior intention. The results show that Habit, Performance Expectancy, and Effort Expectancy are the key factors impacting individual behavioral intention to get mobile investment. These findings will assist researchers and professionals in understanding why individuals utilize mobile investment apps. More importantly, this study's recommendations will help utilize these aspects to enhance these apps’ benefits.